PERAN HUKUM DALAM MENDORONG PEMBANGUNAN BERKELANJUTAN DI INDONESIA - Risnandar, Ahmad; Eka Pratiwi, Desi; Pribadi, Handi; Melyawati, Cahyani; Firmansyah, Ihsan; Yunus Andianto, Agung; Ruslina, Elli (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
This research aims to analyze the role of law in promoting sustainable development in Indonesia. The main principles of sustainable development include: Intergenerational Justice: Ensuring that development activities carried out today do not damage or deplete natural resources so that future generations still have sufficient access to meet their needs. The role of law in supporting sustainable development is critical as it serves as a regulatory framework that helps ensure that development activities not only meet current needs but also consider long-term environmental, economic and social impacts. Without strong enforcement, there is a risk of violations that can damage the environment and hinder the achievement of sustainable development goals. Enforcement includes monitoring, sanctioning and mechanisms to ensure compliance.Keywords: Role of Law, Sustainable development, Law enforcement